Research on microstructure and hardness of AISI1050 disk based on FDM and FEM methods during quenching process. Issue 2 (April 2021) - Zhang, Yishuai; Fu, Jia; Sun, Hongxing; Liu, Hua
Abstract: Microstructures of AISI1050 disk during quenching were simulated by DEFORM-HT, and corresponding parameters of mechanical properties were investigated by applying the algorithm of finite difference method (FDM). Above all, thermo-physical parameters and diagrams of CCT curve were calculated by JMATPRO. Besides, the simulation of multi-phase microstructure considering initial thermo-physical parameters was realized by DEFORM-HT. The volume fraction of single phase were obtained by the FDM method, and then a weight function considering carbon equivalent of phases was introduced to predict the final hardness of multi-phase and according to the quenched microstructure and independent single phase hardness simulated. Temperature field, stress field and microstructure change of an AISI1050 disk under different quenching processes were studied by using the DEFORM-HT software numerical simulation calculation, combined with the continuous cooling transition curve ( CCT curve) of AISI1050 steel. The martensite transformation of the disk tread during the quenching process can increase the wear resistance. According to the actual working conditions combined with the CCT curve of AISI1050 steel, the hardness of the disk rim surface is 54.8 HRC, which can meet the requirements of 51-56 HRC. It is concluded that the maximum equivalent stress of the disk( the equivalent stress after unloading is the residual stress) is distributed near the disk inner layer in the inside of the plate to hand over the location. The microstructure of the specimen is observed and compared with the simulation results, which prove that the simulation results are reliable. The simulated hardness by using both JMATPRO and DEFORM-HT can provide some basis to predict the hardness on certain degree.